Business Information Systems Workshops : BIS 2017 International Workshops, Poznan, Poland, June 28-30, 2017, Revised Papers - Abramowicz, Witold (Springer, 2017)
This book constitutes revised papers from the three workshops and two accompanying events which took place at the 20th International Conference on Business Information Systems, BIS 2017, held in Poznań, Poland, in June 2017. The workshops included in this volume are: * The 9th Workshop on Applications of Knowledge-Based Technologies in Business - AKTB 2017 accepted 9 papers from 16 submissions and features 1 invited paper. * The 8th Workshop on Business and IT Alignment - BITA 2016 selected 5 papers from 10 submissions. * The 1st Workshop on Sustainable Energy Systems, Smart Infrastructures, and Smart Environments - SESSISE 2017 selected 2 papers for inclusion in this book. In addition, BIS hosted a Doctoral Consortium of which 5 papers are included. Furthermore, two contributions from the Second National Congress on Information Systems, that took place during BIS, are included. The volume ends with an invited paper presented during a special session of the main BIS conference.
Keywords: Business -- Data processing -- Congresses.; Management information systems -- Congresses.; Data mining -- Congresses.; elektronické knihy; electronic books